1998
DOI: 10.1159/000008592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Hormone and Insulin-Like Growth Factor-I on Radiation Enteritis

Abstract: The effect of growth hormone (GH) and insulin-like growth factor-I (IGF-I) on intestinal mucosal integrity and bacterial translocation after abdominal radiation was studied in rats. Animals were divided into the following groups: I (control), II (radiation), III (radiation plus GH) and IV (radiation plus IGF-I). Radiation (1,100 cGy) was administered on the 1st day to groups II, III and IV. GH [0.25 mg/kg body weight (BW) s.c. once daily] was administered on days 1, 2 and 3 to group III, and IGF-I (0.1 mg/kg B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…On the other hand, somatostatin analogs not only inhibit the secretion of pancreatic enzymes but also, as shown previously (12), reduce the production of insulin-like growth factor 1 (IGF-1) and growth hormone (GH). Both IGF-1 and GH have been suggested to protect against radiation-induced intestinal and hematopoietic injury by promoting of the proliferation of progenitor cells (25, 26), and somatostatin analogs are known to inhibit of progenitor cell proliferation (27). It is possible that the lack of additional improvement in survival with the “ultra-high” dose of SOM230 (5 mg/kg bid) may have been due to an excess inhibition of hormones, cytokines or stem cells that would otherwise contribute to the regeneration of radiation-injured tissues (28, 29).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, somatostatin analogs not only inhibit the secretion of pancreatic enzymes but also, as shown previously (12), reduce the production of insulin-like growth factor 1 (IGF-1) and growth hormone (GH). Both IGF-1 and GH have been suggested to protect against radiation-induced intestinal and hematopoietic injury by promoting of the proliferation of progenitor cells (25, 26), and somatostatin analogs are known to inhibit of progenitor cell proliferation (27). It is possible that the lack of additional improvement in survival with the “ultra-high” dose of SOM230 (5 mg/kg bid) may have been due to an excess inhibition of hormones, cytokines or stem cells that would otherwise contribute to the regeneration of radiation-injured tissues (28, 29).…”
Section: Discussionmentioning
confidence: 99%
“…Si mi lar fin dings we re al so demons tra ted in ot her stu di es. 4,5,28,29 The lo ca li za ti on of pan cad he rin im mu no re ac ti vity was shown in nor mal in tes ti nal tis su es in our pre vi o us stu di es. 30,31 For the first ti me, the pre sent study de ter mi ned the lo ca li za ti on of pan cad he rin im mu no re ac ti vity in small in tes ti ne of ir ra di a ted rats, as well as the effects of ra di op ro tec ti ve agents on pan cad he rin immu no re ac ti vity.…”
Section: Discussionmentioning
confidence: 59%
“…2,3 Bac te ri a and en do to xins pass thro ugh the distrupted mu co sal barri er and en ter ex tra-in tes ti nal tis su es as well as the blo ods tre am. 4 Af ter ab do mi nal ra di a ti on, dis rup ti on of morp ho lo gic mu co sal in teg rity and nor mal bac teri al mic rof lo ra le ad to ma lab sorb ti on. 5 Di arr he a, vomi ting, ab do mi nal cramps and we ight loss are the comp la ints of the pa ti ents du ring and fol lo wing radi a ti on tre at ment of ab do mi nal and gyne co lo gi cal ma lig nan ci es.…”
Section: K Ke Ey Y Wmentioning
confidence: 99%
“…The average calculated rat dose at the center of the field was 450 cGy/min. Previous studies have shown these parameters to be reliable and reproducible to study the effects of radiation enteritis without mortality until the fourth day after radiation, at which time the progressive effects of mucosal atrophy and ulceration are significant (Alexandrides et al,1998).…”
Section: Methodsmentioning
confidence: 99%